Racial Biases in Officers' Decisions to Frisk Are Amplified for Black People Stopped Among Groups Leading to Similar Biases in Searches, Arrests, and Use of Force. Issue 6 (August 2020) - Cooley, Erin; Hester, Neil; Cipolli, William; Rivera, Laura I.; Abrams, Kaitlin; Pagan, Jeremy; Sommers, Samuel R.; Payne, Keith
Violent encounters between police and Black people have spurred debates about how race affects officer decision-making. We propose that racial disparities in police–civilian interactions are amplified when police interact with Black civilians who are encountered in groups. To test this possibility, we analyzed New York City stop and frisk data for over 2 million police stops. Results revealed that Black (vs. White) people were more likely to be frisked, searched, arrested, and have force used against them. Critically, these racial disparities were more pronounced for people stopped in groups (vs. alone): Being stopped in a group led to a 1.7% increase in racial disparities for frisks, a 1% increase for searches, a 0.3% increase for arrests, and a 1.7% increase for use of force. Moreover, these disparities held even when we controlled for a potential proxy of effective policing: discovery of illegal contraband. We conclude that groups amplify racial disparities in policing.